Children’s Protection in The Issue of Hadhanah Based on Islamic Law Perspective - Prayudi Rahmatullah; Faradiba Suryaningrum; Endang Sulastri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
Every year, the divorce rate in Indonesia continues to grow. Based on data released by the Central Bureau of Statistics (BPS) through the katadata database in early 2020, the divorce rate from 2015 has increased until 2019. In 2019 there were 408,202 cases of divorce. The high rate of divorce certainly has an impact on the lives of both partners, one of which is the issue of child custody or in Islam it is called hadhanah. A child who is still unable to take care of his life until adulthood must be cared for or given a decent life by their parents. Child custody is always an issue between the mother and father when they decide to divorce. Caring for and looking after children who are victims of divorce is obligatory for both parties. The research method used is qualitative normative. The result of this research is that the issue of hadhanah or child custody has been described in detail in the Compilation of Islamic Law in our country. If there is a dispute in this hadhanah issue, it can be resolved by arbitration.